Visible light-driven highly-efficient hydrogen production by a naphthalene imide derivative-sensitized TiO2 photocatalyst - Wei Dan; Yang Kang; Jia Chunman; Li Jianwei (ROYAL SOC CHEMISTRY, 2025)
Sensitizing titanium dioxide (TiO2) with dye molecules offers a cost-effective and environmentally friendly strategy for creating powerful photocatalysts for hydrogen production by reducing the band gap and enhancing sunlight absorption. Despite the challenges of identifying a stable dye with high light harvesting efficiency and effective charge recombination, we present a 1,8-naphthalimide derivative-sensitized TiO2 that achieves ultra-efficient photocatalytic hydrogen production (10.615 mmol g-1 h-1) and maintains activity after 30 hours of cycling. Our research offers valuable insights for designing optimized organic dye-sensitized photocatalysts, advancing clean and sustainable energy solutions.